POLITENESS BEYOND UNIVERSALITY: FACE-THREATENING ACTS AND CULTURAL SYMBOLISM IN MUNA KABHANTI - Lufini, Andi Wardatul Wahidah (ppjbsip, 2026)
This study explores politeness strategies in Kabhanti, a traditional oral performance of the Muna peoplein Southeast Sulawesi, Indonesia. As a dialogic and competitive poetic exchange, Kabhanti is rich in satireand face-threatening acts (FTAs), yet it is socially accepted as a form of legitimate communication thatmaintains rather than disrupts harmony. Using a descriptive qualitative approach, the study draws oninterviews with cultural practitioners and textual analysis of Kabhanti lyrics, interpreted through Brownand Levinson’s (1987) politeness theory. Findings reveal two major strategies: (1) on-record mitigation,evident in euphemisms and hedging to soften direct statements, and (2) off-record strategies, especiallyin Kabhanti with implicature and symbolic cultural references, where meaning is conveyed indirectlythrough metaphor and local symbols. These strategies allow speakers to express critique, rejection, orsarcasm while preserving relational balance. Importantly, the study highlights the limits of Brown andLevinson’s claim to universality: in the Muna context, satire and indirect criticism function as tools ofsocial intelligence, patience-testing, and cultural solidarity rather than threats to face. This suggests thatpoliteness theory must be contextualized within specific cultural frameworks, where FTAs can serveconstructive social roles. The study contributes to cross-cultural pragmatics by illustrating how indigenoustraditions challenge Western-centric models of politeness. Future research should examine thetransformation of Kabhanti in modern contexts, including its role in education, cultural preservation, andintercultural communication.